The Role of Light In The Architecture of Religious Buildings - Iskandar, Iskandar; Zacky, Zulfan; Ratika Isti, Adelina; P. Agustiananda, Putu Ayu; Budiman, Hanif (Devotion : Journal of Research and Community Service, 2023)
Light is one of the important factors in human life. Lighting especially in houses of worship is considered a very important part for symbolic and spiritual reasons. Light is the main focus in architecture, both in Islamic and Gothic architecture. The purpose of this study is to summarize the role of light in buildings of worship, especially houses of worship.  This study uses a qualitative method of literature study. The results of this study indicate that the role of light in buildings of worship, especially houses of worship, is very important for the congregation, both spiritually and visually. Spiritually, the role of light can provide inner peace and also the closeness of the servant to his God. from a visual point of view the role of light can provide beauty and comfort to the room. From these results, the conclusion is that the role of light in religious buildings in the building of houses of worship is very important for worshippers, in shaping the inner kayakinan both in spiritual terms and in Visual terms